Sharia Financial Literacy, Halal Lifestyle, and Islamic E-Wallet Adoption Among Students - M. Arianda Ihza Firmanadi; Cholisa Rosanti (CV Putra Publisher, 2026)
This study aims to analyze the effect of Islamic financial literacy on the intention to use Islamic e-wallets and halal lifestyle, as well as to examine the mediating role of the Theory of Planned Behavior (TPB) among cadres of Ikatan Pelajar Muhammadiyah (IPM) in Pekalongan City. This study employed a quantitative approach using an explanatory research design, involving 50 respondents selected through purposive sampling from 100 active IPM cadres. Data were collected using a Likert-scale questionnaire and analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The results indicate that Islamic financial literacy has a significant positive effect on the intention to use Islamic e-wallets (β = 0.498; p = 0.021) and halal lifestyle (β = 0.508; p = 0.009). The primary finding of this study is the evidence of full mediation by TPB in the relationship between Islamic financial literacy and the intention to use Islamic e-wallets, with an indirect effect of 0.427. Islamic financial literacy explains 58.1% of the variance in TPB, confirming that attitude, subjective norm, and perceived behavioral control serve as the dominant psychological mechanisms shaping digital Islamic financial behavior among young Muslims. This study contributes to the development of a TPB-based Islamic financial literacy model and provides practical implications for IPM cadre development within the context of digital Islamic financial inclusion. This study offers novelty by integrating Islamic financial literacy, halal lifestyle, and the Theory of Planned Behavior (TPB) within the context of Islamic e-wallet adoption among IPM student cadres, a group that has received limited attention in previous Islamic finance studies.